Panel Discussions to Promote Meaningful Learning at Distance Education - Paredes, Fabian; Salcedo-Viteri , Karina; Pinza-Tapia, Eliana; Toro, Vanessa (IJET (Indonesian Journal of English Teaching), 2023)
The present mix-method study was carried out with the purpose of promoting meaningful learning through panel discussion to enhance students´ active participation in English. It was conducted at a private university in its distance modality. The sample of the study was 52 students from different provinces of Ecuador and 2 teachers. The data-collection instruments were two questionnaires and an observation grid. These were designed to learn if the use of panel discussions promotes meaningful learning and also to identify the students’ level of satisfaction regarding the use of panel discussions. The questionnaires were applied after 8 panel discussions were held. The observation grid was used by the teachers during each panel to take notes about aspects such as motivation, comprehension, and functionality. The findings demonstrate that students’ level of satisfaction was high regarding the use of panel discussions since they helped to increase their motivation to actively participate by using previous experience with new knowledge.